EFEKTIVITAS PERTANYAAN PENGARAH TERHADAP PENGUASAAN KONSEP DAN RETENSI SISWA DALAM PEMBELAJARAN BIOLOGI - Rahman, Taufik; Rochintaniawati, Diana (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2001)
Questioning plays an important role in teaching learning process. The effect of prompting question and non-prompting question in biology teaching learning process on increasing studentâs understanding and studentâs retention was evaluated in this study.Â The method used in the study was experimental involving students in control group who used student experiment and non-experiment worksheet without prompting question and students in experimental group who used student experiment and non-experiment worksheet with prompting question. The study was carried out in 4 concepts, i.e. the environment sustainability, water pollution, environment study, as well as sight organ in Invertebrate. To evaluate the different effect of student worksheet with prompting question and student worksheet without prompting question on increasing studentâs understanding and retention posttest 1 and post-test 2 was given to the two groups in time interval of 2,3 and 4 weeks. From the result of the two tests the retention was measured. The study revealed that in the concept of Environment sustainability, environmental study and water pollution the use of student worksheet with prompting question as well as without prompting question was effectively increased studentâs understanding to the concept, and the increasing of studentâs understanding to the concept between control and experiment group was equally the same. Meanwhile in the concept of the organ sight in invertebrate the use of experiment student worksheet with prompting question more effectively increased studentâs understanding to the concept than the use of experiment student worksheet without prompting question. Student in the experiment group performed better retention on the concept than student in control group.